The effectiveness of object-oriented-QR Monopoly in enhancing ice-breaking and education UX: A preliminary study - Lee, Chien Sing * (Asia-Pacific Society for Computers in Education, 2021)
With increasing COVID cases, many are studying or working from home. We aim to address two problems. First, since many companies are into reskilling and upskilling in groups, the human touch and community are important. One aspect of human touch and community development, is ice-breaking. Second, we need to enable easy customization to reuse the objects or assets for different scenarios, contexts and needs. We are interested in games. Hence, a third problem we want to address is to improve problem-solving competencies through games. Our scope of work is to investigate the effectiveness of an object-oriented QR Monopoly game, to enhance ice-breaking in online training, and for education. Preliminary user testing indicates positive findings, with regards to the inclusion of chance, theme/rules/process/asset/switching/modification, adding on to computer playfulness via object-orientation of the QRMonopoly game and entity-process modeling.